Analysis of the Influence of Competency and Motivation on Employee Performance in Government Agencies in Medan City - Muhammad Alfahmi; Muhammad Albahi; Muhammad Alfikri (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study aims to analyze the influence of competence and motivation on employee performance in government agencies in Medan City. The type of research used is quantitative with a survey method. The data was collected through a questionnaire distributed to 226 employees from five government agencies in Medan City. Data analysis was carried out using multiple linear regression with the help of the SPSS version 26 program. The results of the study show that competence has a positive and significant effect on employee performance, as well as motivation has a positive and significant influence. Simultaneously, competence and motivation contribute 62.2% to employee performance, while the rest are influenced by other factors such as work environment and leadership. These findings reinforce the theory that optimal performance is achieved through a balance between technical ability and motivation for work. Therefore, the Medan City Government is advised to strengthen competency development programs and create an effective motivation system to improve the performance of apparatus and the quality of public services.